(untitled) (Perner’s Contacts, 2012)
The issue of transport provision in the process of solving critical phenomena is very extensive. It has its own specifics in crisis planning in defense planning, in civil emergency planning, in a time of mobilization, and so on. The transport provision of solutions critical phenomena is in this paper mainly focused on the removal of people and animals from the endangered area as an integral part of civil emergency planning in crisis management in the Slovak Republic.